2006
DOI: 10.1161/01.str.0000227191.01792.e3
|View full text |Cite
|
Sign up to set email alerts
|

Alteplase at 0.6 mg/kg for Acute Ischemic Stroke Within 3 Hours of Onset

Abstract: In patients receiving 0.6 mg/kg alteplase, the outcome and the incidence of sICH were comparable to published data for 0.9 mg/kg. These findings indicate that alteplase, when administered at 0.6 mg/kg to Japanese patients, might offer a clinical efficacy and safety that are compatible with data reported in North America and the European Union for a 0.9 mg/kg dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
339
7
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 480 publications
(362 citation statements)
references
References 42 publications
15
339
7
1
Order By: Relevance
“…However, as pointed out by a recent review [23], the doses used in Asia are more diverse. After the Japanese Acute Stroke Trial [24] which demonstrated the efficacy of 0.6mg/ kg alteplase with fewer hemorrhagic complications, various Asian countries have adopted lower doses of alteplase for their patients. This precludes effective comparisons between various Asian cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…However, as pointed out by a recent review [23], the doses used in Asia are more diverse. After the Japanese Acute Stroke Trial [24] which demonstrated the efficacy of 0.6mg/ kg alteplase with fewer hemorrhagic complications, various Asian countries have adopted lower doses of alteplase for their patients. This precludes effective comparisons between various Asian cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Eligibility for inclusion in this study was that patients met the following criteria: 1) They had an acute anterior circulation stroke with angiographically confirmed ICA-T or -L (-T or -L indicate the shape of occlusive lesion), MCA M1, or ICA/M1 tandem occlusion; 2) had evaluable angiographic imaging for collateral-flow grading; 3) had arterial puncture in the angiography suite room within 8 hours from time last-known well; and 4) achieved a sufficient angiographic reperfusion, which we defined as a TICI grades 2-3 (Fig 1). 13 Within the 3-hour time window, intravenous rtPA was used, 14,15 and patients showing a persistent ICA or MCA occlusion despite rtPA on TOF MRA or CTA were selected for endovascular treatment. We excluded patients who revealed well-developed parenchymal hypoattenuation on CT or hyperattenuation on FLAIR imaging, severe brain edema, intracerebral hemorrhage, or cardiopulmonary compromise.…”
Section: Methodsmentioning
confidence: 99%
“…6 Yamaguchi T et al concluded that "alteplase, when administered at 0.6 mg/kg to Japanese patients, might offer a clinical efficacy and safety that are compatible with data reported in North America and the European Union for a 0.9 mg/kg dose." 7 Schellinger PD et al compared "MRI based thrombolysis" with "CT based thrombolysis". 8 They concluded that "MRI based thrombolysis" was more effective and safer than the "CT based thrombolysis".…”
Section: Discussionmentioning
confidence: 99%